Konya Valisi Mehmed Ferid Paşa’nın Gözünden Antalya (1898-1902) - Hatice DURGUN (Gazi Akademik Bakış)
At the end of the 19th century, Antalya was a sanjak of Konya Province and contrary to its hinterlands, it had significant agricultural resources due to its fertile lands. During the 19th century, the city's expected commercial productivity was not achieved despite its great commercial potential due to its natural port. The failure to fulfil its great potential also stemmed from its disadvantageous geographical location and the lack of reformist and far-sighted administrators to solve the problems encountered and meet the needs of the locals. As one of the hardworking and successful administrators of the reign of Sultan Abdulhamit II, Mehmed Ferid Pasha of Avonya was appointed as the governor of Antalya, and this provided an excellent opportunity for the city to prosper. Mehmed Ferid Pasha served as the governor of Konya between 1898 and 1902, and during his four-year term in office, he managed to change the portrait of the city positively. Mehmed Ferid Pasha was particularly interested in Antalya and visited the city four times to inspect its problems and needs. These inspections were also followed by comprehensive research and examination of solutions for the problems and meeting the demands of the locals. As the main aim of the study, all those visits, inspections and research culminated in a series of detailed reports that revealed the reason why Antalya failed to fulfil its real potential at the beginning of the 20th century. As a meticulous administrator, the problems that Mehmed Ferid Pasha put forward regarding Antalya and his contribution to finding solutions for these problems were significantly influential in drawing the general framework of this study. The determination of the extent to which prosperity, settlement, agriculture and education problems of Antalya could be solved was revealed in the direction of the documents obtained from the Ottoman Archives.